Metaphoric consideration of the UKRAINE concept significance in the non-Ukrainian journalistic discourse and its influence on social and linguistic consciousness – A corpus research of the 2022-2025 wartime period - Vitalii Stepanov; Olena Yemelianova; Svitlana Baranova; Maryna Nabok (East European journal of psycholinguistics, 2025)
The article studies associations of the Ukrainian topic in non-Ukrainian journalistic sources of the 2022-2025 wartime period to define how importance of Ukrainian support is regarded from the worldwide safety perspective. The research relies on heritage of the Ukrainian cognitive linguistics where concept is treated as a dynamic layer unity of notion, image and values, which develops in the constantly evolving discourse as social and linguistic consciousness with a changeable public attitude to its essence. The research is conducted via corpus as a mini-model of discourse. The News on the Web (NOW) Corpus is selected as the most authentic base of permanently updating resources since 2010 till today. 122 journalistic sources are taken from the NOW Corpus to produce a 230-context sample of Ukrainian metaphoric associations in the non-Ukrainian press. The sample is processed via the Lakoff-Johnson conceptual metaphor methodology to provide a list of images non-Ukrainians associate Ukraine with. All 421 detected cases of metaphoric associations are sorted by decreasing frequency in mental clusters (law, biology, structure, labor, psychology, science, economics, art and leisure, interpersonal communication). It produces a metaphoric spectrum from the most to least relevant images of the UKRAINE concept within the non-Ukrainian community. Consequently, UKRAINE is associated as ORGANISM; HUMAN; BUILDING; WARRIOR; LEGAL STATUS. Moderate considerations are reflected via metaphors UKRAINE as GAME; VICTIM; MACHINE; PHYSICAL BODY; OWNER; PARTNER; TARGET; OFFENDER; PRODUCT. The least frequent metaphors are UKRAINE is TEAM; FRAGMENTED OBJECT; COMPLEX OBJECT; SINGLE OBJECT; PROPERTY; IDEA; AUTHORITY; JESUS CHRIST; ANIMAL; PLANT; VEHICLE; FAMILY; CONSUMER; RESOURCE; LIQUID; SOLID; DEBTOR; ACCUSER; LEGAL SUBJECT; FLAME; LESSON; WRITTEN TEXT; PASSENGER; SCALES; GARMENT; GLASSWARE; PICTURE; RESEARCHER; EQUATION; RIVAL; BOMB. The results are open for specification (new samples of the UKRAINE concept may be processed because the war is not over and future non-Ukrainian associations may differ, respectively). Acknowledgements The study has been carried out under the project Commemoration of the Russian-Ukrainian War within the State Humanitarian Policy: Formation of a Sustainable Model of Ukrainian Society Consolidation funded by the Ministry of Education and Science of Ukraine, State Reg. No. 0121U112686, Funding contract No. БФ/23-2021. As project performers, Vitalii Stepanov, Olena Yemelianova and Maryna Nabok greatly appreciate research supervision, advice and support of Svitlana Baranova, an article co-author and representative of another Sumy State University project (grant of the National Research Foundation of Ukraine Innovative Technologies of the Mass Consciousness Manipulation: A Polyparadigmatic Linguistic Dimension, State Reg. No. 0124U004832). Disclosure Statement The authors reported no potential conflict of interests.